A review of the literature on the issues and roles of E-Learning in UAE higher education - Alblooshi, Saeed; Abd Hamid, Nor Aziati (American Scientific Publishers, 2019)
E-Learning is becoming a popular delivery method across various universities and colleges in UAE as the region is experiencing a rapid growth of e-Learning in higher education. Adequate infrastructure, changes in demographic profile, globalization, government initiatives, outsourcing and increasing demand for IT knowledge-based jobs are the major factors responsible for e-Learning growth in higher education in UAE. However, e-Learning has many problems such as inadequate equipment, improper guidance on using e- Learning gadgets, inadequate infrastructure, changes in demographic profile, globalization, inadequate government initiatives are the major problems of e-Learning growth in higher education in UAE. Based on this review, e-Learners have shown indeed a very high level of understanding concerning the potential and value of e-Learning. It is anticipated that the findings of this study will offer opportunities to improve policy and practice of e-Learning in higher education in the UAE so as to solidify its position as an e-learning hub in the gulf region.